Melanotic neuroectodermal tumour of infancy: A case report - Retna Kumari N; Sreedharan S; Balachandran D (Wolters Kluwer Medknow Publications, 2007)
A case of melanotic neuroectodermal tumor of infancy occurring in the maxilla in a 13 day old neonate is described. Computed tomography and histopathology confirmed the diagnosis and a submucosal excision was carried out when the infant was 30 days old. But three weeks later the patient reported back with a recurrence and a wide surgical excision was performed. The recurrence may have been caused by incomplete removal of the tumor cells and the initial surgical procedure may have stimulated tumour cell proliferation. Fortunately, 6 month follow up of the patient showed no recurrence.